Room Temperature Polariton Lasing in Ladder‐Type Oligo(p‐Phenylene)s with Different π‐Conjugation Lengths. Issue 1 (23rd November 2020) - Wei, Mengjie; Fang, Mei; Rajendran, Sai Kiran; Lai, Wen-Yong; Turnbull, Graham A.; Samuel, Ifor D. W.
Abstract : Polariton lasing is coherent emission that originates from macroscopic accumulation of polariton population in the ground state and is a promising route toward efficient coherent light sources as population inversion is not necessary. Unlike most Wannier–Mott excitons in inorganic semiconductors, Frenkel excitons created in organic semiconductors have high oscillator strength and high exciton binding energy, which sustain stable exciton–polaritons at room temperature. Herein, room temperature polariton lasing from a novel class of ladder‐type oligo( p ‐phenylene)s is demonstrated. The polariton lasers exhibit a nonlinear increase of their spectrally integrated emission, a reduction in spectral linewidth, blueshift of emission peaks, and long‐range spatial coherence when the pump fluence is increased above threshold. By tuning the π‐conjugation length of the molecular structure, the polariton lasing wavelength can be changed from 430 to 457 nm. Optically pumped thresholds of 12 and 17 μJ cm −2 are observed, which are among the lowest values reported for polariton lasing in organic semiconductors. Abstract : Room temperature polariton lasing is demonstrated in ladder‐type oligo( p ‐phenylene)s at thresholds of 12 and 17 μJ cm −2 . By increasing the π‐conjugation length along molecular backbone, an extra vibronic excitonic transition is involved in strong coupling with photons, and a polariton lasing wavelength is tuned by 27 nm, indicating a potentially broad tunability of lasing wavelength by tailoring conjugation length.